Application of artificial landmark in sonar detection. (1st August 2022) - Li, Jianda; Tang, Zhijie; Wang, Zhanhua; Huang, Jingke; Wang, Chi
Abstract: Sonar is an important means of underwater target detection. However, the existing sonar measurement method does not use a third-party object as a reference, which makes it difficult to measure underwater targets. In this paper, we propose an angle measurement method and a 3D mapping algorithm based on sonar images and artificial landmarks. By combining acoustic and visual methods, using the known size information of artificial landmarks as a reference, we can calculate the target information to realize the mapping between real space and sonar images. Before verifying the feasibility, we processed the sonar image, denoised it with a median filter, enhanced the landmark image with the Sauvola algorithm, and finally introduced two data fitting methods to extract the edge information of artificial landmarks, so as to help us find the key points more accurately. The experimental results show that the accuracy of our method can reach the millimeter level, and the error range is within 5%. The technology proposed in this paper realizes the shape correction and precise length measurement of underwater targets.